CONTAINER-BASED VIRTUALIZATION FOR BLOCKCHAIN TECHNOLOGY: A SURVEY - Nawar A. Sultan; Rawaa Putros Qasha (Jordanian Journal of Computers and Information Technology, 2023)
Blockchain technology has garnered interest in several scientific and engineering fields. To improve blockchain services, its execution challenges must be addressed. Container-based virtualization enables running isolated apps on a shared OS where blockchain technology can leverage this technology to run numerous nodes, smart contracts, and decentralized apps in distinct containers allowing resource isolation and allocation, faster deployment and scalability, and improved security through limited host OS and other container access. This article covers container-based virtualization for Blockchain technology, including current methodologies, prospects, and future perspectives. Initially, this study explains blockchain and containerization as well as the reason for their integration. Then reviews container virtualization services to address blockchain complexity, size, scalability, and security. Conversely, Container technology uses blockchain to protect data and enhance resource management. Next, analyzes the latest containerization and blockchain integration studies. Finally, difficulties and future directions are considered to advance this promising research. [JJCIT 2023; 9(3.000): 235-248]